2018
DOI: 10.18203/2320-1770.ijrcog20183431
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for bacterial vaginosis in sexually active females in age group 20-45 years and comparison of Amsel's criteria with Nugent's score

Abstract: Background: In recent years Bacterial vaginosis has emerged as a global issue of concern due to its association with cervicitis, salphingitis, endometritis, postoperative infections, Urinary tract infections, pelvic inflammatory infections, spontaneous abortions, preterm delivery, abnormal Pap smears and increased susceptibility to HIV. Bacterial vaginosis is one of the most common lower genital tract infections among women of childbearing age and yet its diagnosis can be problematic. Gardnerella has been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…However, this study has further revealed that in consistent with previous studies that the highest prevalence of bacterial vaginosis occurred in women within the reproductive age. These women are also the most sexually active and studies have shown that they have the highest rate of pregnancies and sexually transmitted diseases [12, 24]. Women who were multiparous and with higher education constituted the highest group with bacterial vaginosis in this study and this is consistent with reports from previous studies [12, 21, 23, 24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, this study has further revealed that in consistent with previous studies that the highest prevalence of bacterial vaginosis occurred in women within the reproductive age. These women are also the most sexually active and studies have shown that they have the highest rate of pregnancies and sexually transmitted diseases [12, 24]. Women who were multiparous and with higher education constituted the highest group with bacterial vaginosis in this study and this is consistent with reports from previous studies [12, 21, 23, 24].…”
Section: Discussionsupporting
confidence: 92%
“…These women are also the most sexually active and studies have shown that they have the highest rate of pregnancies and sexually transmitted diseases [12, 24]. Women who were multiparous and with higher education constituted the highest group with bacterial vaginosis in this study and this is consistent with reports from previous studies [12, 21, 23, 24]. This was attributed to increased coital frequency and douching which might result in reduction in the physiological barrier in the vaginal and overgrowth of normal commensals [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated to be between 25-50% in sub-Saharan African countries [7]. It can occur in any age group, but in particular, it is more prevalent among women of childbearing age [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the epidemiological profile of women with BV is similar to that of women with STIs: BV is significantly associated with having a recent sexual partner or multiple sexual partners [38]. In the study by Ghattargi et al, BV was more common in multiparous women with a statistically significant difference [39].…”
Section: Discussionmentioning
confidence: 96%
“…Cases of BV were more frequent among women in the (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) [20].…”
Section: Discussionmentioning
confidence: 99%